COVID-19 Contact Tracing Apps and Technologies as a tool of Mass Surveillance: A Cure Deadlier than the Disease - Bashar, Arafat Ibnul (Kathmandu School of Law Review, 2020)
“Desperate times call for desperate measures” – COVID-19 contact tracing apps and technology have been operating in the desperate times created by the COVID-19 global pandemic. But the impact of these apps and technology on society is contentious, as the benefit gained from such is said to be largely outweighed by the negative impact it can have during and after the pandemic. Surveillance measures have always been a tricky business. Labeled as the ‘magical solution’ for most horrid problems of our time such as terrorism, crime prevention, it has always failed to live up to its name and has proved to be one of the prominent tools for the authoritarian regimes to oppress people and commit gross human rights violations. Over-reliance on COVID-19 apps and considering them a ‘magical solution’ to containing the spread of Coronavirus can have irreversible consequences. Instead, the pandemic and desperate situation posed by it may have provided the regimes around the world an opportunity to introduce new surveillance infrastructures or strengthen the existing ones, which would have taken years and lots of friction from courts, activists, and civil society, to achieve. The article assesses the legality of COVID-19 contact tracing apps and technology and tries to draw a picture of the society that faces the consequences of surveillance and data collected through such apps and technology and looks at how legal mechanisms can cope with such consequences.